2022
DOI: 10.3390/polym15010170
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Carbon Fiber from Carbon Fiber-Reinforced Polymer and Its Reuse in Photocatalysis: A Review

Abstract: Driven by various environmental and economic factors, it is emerging to adopt an efficient and sustainable strategy to recycle carbon fibers (rCFs) from carbon fiber-reinforced polymer (CFRP) wastes and reuse them in high-value applications. This review summarized the latest progress of CFRP waste recycling methods (including mechanical, chemical, and thermal methods), discussed their advantages and disadvantages, influence parameters and possible environmental effects, and their potential effects on the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 144 publications
0
3
0
Order By: Relevance
“…The mechanical and chemical cycling processes involved subjecting the samples to repeated mechanical loading and exposing them to certain chemical treatments to simulate real-world conditions and assess their durability. The Universal Testing Machine played a crucial role in evaluating the mechanical properties of the composite material [67,68]. It allowed for precise measurements of parameters such as tensile strength, elastic modulus, and yield strength.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanical and chemical cycling processes involved subjecting the samples to repeated mechanical loading and exposing them to certain chemical treatments to simulate real-world conditions and assess their durability. The Universal Testing Machine played a crucial role in evaluating the mechanical properties of the composite material [67,68]. It allowed for precise measurements of parameters such as tensile strength, elastic modulus, and yield strength.…”
Section: Methodsmentioning
confidence: 99%
“…There is a lack of research on the crushing equipment and its effectiveness, as well as studies involving fill ratios exceeding 30 wt.%. 11,25 In this study, we utilized the self-developed solid-state shear milling (S3M) method [26][27][28] to transform waste wind turbine blades into a value-added powder with reinforcing capabilities. The unique three-dimensional shear forces generated by S3M technology proved to be highly effective in removing epoxy adhesion from the glass fiber surface and reduce the size of epoxy particles.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been limited research on mechanical recycling methods, with the majority of studies still following a simplistic approach of crushing and sieving, followed by blending with thermoplastic polymers. There is a lack of research on the crushing equipment and its effectiveness, as well as studies involving fill ratios exceeding 30 wt.% 11,25 …”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin is widely used as a matrix material in the preparation of carbon fiber-reinforced polymer composites (CFRPs), but the growing production of CFRPs has raised concerns regarding waste management and the recycling of high-value carbon fibers. Unfortunately, recovering carbon fibers from CFRPs is particularly challenging. The traditional mechanical, thermal, and chemical methods impact the performance of carbon fibers and raise environmental and health concerns . In contrast, recent studies have shown that the development of biobased epoxy resins with exceptional recyclability and degradability is crucial for the advancing sustainable CFRPs. , …”
Section: Introductionmentioning
confidence: 99%